2015
DOI: 10.7326/m15-0333
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia miyamotoi Disease in the Northeastern United States

Abstract: IMUGEN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
178
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(199 citation statements)
references
References 26 publications
12
178
1
8
Order By: Relevance
“…It now appears that hard tick-borne relapsing fever may be an exception in this respect: our experimental demonstration of transmission of B. miyamotoi by larval ticks supports the idea put forth in epidemiological studies (Molloy et al, 2015; Fiorito et al, 2017) that transovarially-infected larvae are involved as vectors of this relapsing fever spirochete to humans in the United States. Pathogen transmission by I. scapularis larvae is especially concerning in the Northeast, where the seasonal timing of peak larval activity (summer) is distinct from that of both peak nymphal activity (late spring) and peak activity of female ticks (fall and early spring).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…It now appears that hard tick-borne relapsing fever may be an exception in this respect: our experimental demonstration of transmission of B. miyamotoi by larval ticks supports the idea put forth in epidemiological studies (Molloy et al, 2015; Fiorito et al, 2017) that transovarially-infected larvae are involved as vectors of this relapsing fever spirochete to humans in the United States. Pathogen transmission by I. scapularis larvae is especially concerning in the Northeast, where the seasonal timing of peak larval activity (summer) is distinct from that of both peak nymphal activity (late spring) and peak activity of female ticks (fall and early spring).…”
Section: Resultssupporting
confidence: 82%
“…The relapsing fever spirochete, Borrelia miyamotoi, is increasingly recognized as a cause of human illness (hard tick-borne relapsing fever) in the United States (Krause et al, 2013, 2014; Molloy et al, 2015; Fiorito et al, 2017). The primary vector of B. miyamotoi to humans in the eastern part of the United States is the blacklegged tick, Ixodes scapularis , which also transmits the Lyme disease spirochetes, Borrelia burgdorferi sensu stricto (s.s.) and Borrelia mayonii (Krause et al, 2015; Breuner et al, 2017; Eisen, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RF Borrelia spirochetes cause a variety of diseases, which are characterized by episodes of high fever separated by periods of relative well-being. The clinical presentation of disease caused by B. miyamotoi, however, appears to differ from that of classical RF, since relapsing-fever episodes have been observed only in 10% of patients infected with B. miyamotoi, and their levels of spirochetemia are calculated to be low (6,7). Since most patients with B. miyamotoi infection are usually treated with antibiotics, this might be an underestimation of the naturally occurring relapses.…”
mentioning
confidence: 99%
“…This suggests a potentially higher contribution of larval tick bites to tick-borne relapsing fever in humans compared to larval contribution to Lyme borreliosis. Other studies have previously suggested an important role for larvae in the transmission of B. miyamotoi based on infections coinciding with larval activity and infestation (Barbour et al 2009, Molloy et al 2015. The contribution of larval transmission to rodents and from rodents to larvae to the enzootic life cycle of B.…”
Section: Discussionmentioning
confidence: 95%